2017
DOI: 10.1086/689891
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Coevolutionary Dynamics in High-Dimensional Phenotype Spaces

Abstract: We study macroevolutionary dynamics by extending microevolutionary competition models to long time scales. It has been shown that for a general class of competition models, gradual evolutionary change in continuous phenotypes (evolutionary dynamics) can be non-stationary and even chaotic when the dimension of the phenotype space in which the evolutionary dynamics unfold is high. It has also been shown that evolutionary diversification can occur along non-equilibrium trajectories in phenotype space. We combine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(97 citation statements)
references
References 60 publications
7
90
0
Order By: Relevance
“…Bounds in trait space and saturation of ecological space exacerbate competition‐driven declines in diversification rates, but are not required: the constraints in phenotypic space imposed by competing lineages is sufficient by itself to slow down diversification as radiations proceed. Although radiating in multidimensional trait spaces might alleviate these constraints (Doebeli & Ispolatov ), if species mostly diversify along single or a few phenotypic axes (e.g. lines of least evolutionary resistance; Schluter ), the described scenario might be common and invocation of contentious hard ecological limits to diversity not needed, favoring ‘damped’ diversification explanations instead (Cornell ; Harmon & Harrison ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bounds in trait space and saturation of ecological space exacerbate competition‐driven declines in diversification rates, but are not required: the constraints in phenotypic space imposed by competing lineages is sufficient by itself to slow down diversification as radiations proceed. Although radiating in multidimensional trait spaces might alleviate these constraints (Doebeli & Ispolatov ), if species mostly diversify along single or a few phenotypic axes (e.g. lines of least evolutionary resistance; Schluter ), the described scenario might be common and invocation of contentious hard ecological limits to diversity not needed, favoring ‘damped’ diversification explanations instead (Cornell ; Harmon & Harrison ).…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to test if novel statistics that capture finer scale variation in a trait’s distribution than Blomberg’s K (e.g. Lewitus et al in press) are also able to distinguish these two scenarios, as well as to check if phylogenetic signal remains a feature of adaptive radiations in multidimensional trait space (Harvey & Rambaut , Doebeli & Ispolatov ). Likewise, it would be useful to assess the robustness of the support for Drury et al .’s MC models (2016) with a variety of competition‐driven radiation scenarios, as it could be argued that our generating model resembles the MC inference tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other traits are also considered, such as the prefered relative size of preys and specialization of predators. In general, higher dimensional trait spaces are known to promote branching (Ispolatov et al, 2015;Doebeli and Ispolatov, 2017). Allometries are also considered in all models, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on the particular case of competing species, ignoring for now other ecological interactions, and consider a diversifying community described by a logistic competition model in which the competition between individuals is controlled by several phenotypic traits. Previously it was shown that in such systems, the dimension of phenotype space affects diversification, with higher dimensions leading to higher diversity (Doebeli and Ispolatov 2017). As a community diversifies from low numbers of species, the rates of evolution and of diversification slow down as the community reaches a saturation level of diversity that the environment can sustain.…”
Section: Introductionmentioning
confidence: 99%